The World as an External Memory: The Price of Saccades in a Sensorimotor Task - Melnik, Andrew; Schüler, Felix; Rothkopf, Constantin A.; König, Peter (Frontiers in Behavioral Neuroscience, 2018)
Theories of embodied cognition postulate that the world can serve as an external memory. This implies that instead of storing visual information in working memory the information may be equally retrieved by appropriate eye movements. Given this assumption, the question arises, how we balance the effort of memorization with the effort of visual sampling our environment. We analyzed eye-tracking data in a sensorimotor task where participants had to produce a copy of a LEGO®-blocks-model displayed on a computer screen. In the unconstrained condition, the model appeared immediately after eye-fixation on the model. In the constrained condition, we introduced a 0.7 s delay before uncovering the model. The model disappeared as soon as participants made a saccade outside of the Model Area. To successfully copy a model of 8 blocks participants made saccade to model area on average 7.9 times in the unconstrained condition and 5.6 times in the constrained condition. However, the mean duration of a trial was 2.1 s (9%) longer in the constrained condition even when taking into account the delayed visibility of the model. In this study, we found evidence for an adaptive shift in subjects’ behavior towards memorization by introducing a price for a certain type of saccades. However, the response is not adaptive; it is maladaptive, as memorization leads to longer overall performance time.